Implication of NF-κB in Helicobacter pylori-associated gastritis - Isomoto, Hajime; Mizuta, Yohei; Miyazaki, Masanobu; Takeshima, Fuminao; Omagari, Katsuhisa; Murase, Kunihiko; Nishiyama, Takashi; Inoue, Ken-ichiro; Murata, Ikuo; Kohno, Shigeru (The American journal of gastroenterology, 2000)
OBJECTIVE: Transcription factor NF-κB plays a pivotal role in inflammatory responses by up-regulating mRNA expression of bioactive molecules such as chemokines and adhesion molecules. The present study was designed to elucidate the implication of NF-κB in Helicobacter pylori–associated gastritis (HAG). METHODS: We examined 41 patients with HAG and 18 H. pylori–negative control subjects. Expression of activated NF-κB was studied in situ by immunohistochemistry using α-p65 mouse monoclonal antibody (α-p65 mAb), which recognizes activated NF-κB. To identify the cell types in which NF-κB was activated, we performed immunohistochemical analysis using antibodies against vascular endothelial cells, macrophages, and B and T lymphocytes. We also examined the colocalization of activated NF-κB with the expression of intercellular adhesion molecule-1 (ICAM-1) on endothelial cells. We measured the levels of NF-κB–dependent chemokines including interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1), regulated on activation normal T-cell expressed and secreted (RANTES) and macrophage inflammatory protein-1α (MIP-1α) in antral mucosa by ELISA (ELISA). RESULTS: Activated NF-κB was detected in the nuclei of epithelial cells in antral mucosa, especially of patients with HAG. NF-κB positivity index (NF-κB PI), representing the percentages of epithelial cells with positive nuclear staining for activated NF-κB, was significantly higher in patients with HAG than in H. pylori–negative controls. NF-κB PI correlated significantly with histological scores of gastritis. Moreover, activated NF-κB was identified in the nuclei of vascular endothelial cells, macrophages, and B lymphocytes within the lamina propria in HAG. Colocalization of activated NF-κB with ICAM-1 expression in the same endothelial cells was demonstrated. The IL-8 levels significantly correlated with the NF-κB PI. CONCLUSIONS: In addition to epithelial cells, macrophages, vascular endothelial cells, and B lymphocytes contained activated NF-κB. In these cells, activated NF-κB may be involved in the inflammation process in HAG through the up-regulation of chemokines or adhesion molecules.